Experimental testing of full-scale glulam frames with buckling restrained braces. (1st November 2020) - Dong, Wenchen; Li, Minghao; Lee, Chin-Long; MacRae, Gregory; Abu, Anthony
Highlights: Full-scale glulam frames with BRBs were tested under cyclic loading. BRBs improve the glulam frames' strength, stiffness and energy dissipation. Two types of timber-steel interface connections were strong and stiff to work with BRBs efficiently. The capacity design approach proved to work well. Abstract: This experimental study investigates cyclic performance of a timber-steel hybrid structural system consisting of glulam frames and buckling restrained braces (BRBs). The BRBs are designed as ductile elements in the hybrid system to dissipate energy under seismic loading. Following the capacity design approach, two full-scale 8 m wide and 3.6 m high BRB glulam frame (BRBGF) specimens were tested. The BRBs were connected to the glulam frames by pins and steel gusset plates. Dowelled connections with inserted steel plates were used in one specimen to connect the glulam members while screwed connections with steel side plates were used in the other specimen. The test results showed that the integration of BRBs into the glulam frames significantly improved the load carrying capacity and energy dissipation. Both BRBGF specimens achieved a minimum ductility factor of 3.0 based on CEN method. The connections and the glulam members were well protected without significant damage. Therefore, the dowelled connections and screwed connections provided solutions to engage BRBs efficiently to resist lateral loads in this hybrid system.